Rural Cancer Survivors' Perceived Delays in Seeking Medical Attention, Diagnosis and Treatment: Findings From a Large Qualitative Study - Alyssa Taglieri‐Sclocchi; Ingrid Bindicsova; Susannah K. Ayre; Michael Ireland; Sonja March; Fiona Crawford‐Williams; Suzanne Chambers; Jeff Dunn; Belinda C. Goodwin; Elizabeth A. Johnston (Cancer Medicine, 2025)
ABSTRACT Aims To investigate rural cancer survivors' self‐reported reasons for perceived delays in initial cancer detection and treatment. Methods Within a cohort study, adult cancer survivors who had travelled > 50 km for cancer care, staying at subsidised accommodation lodges in city centres in Queensland, Australia, were invited to complete a structured interview on perceived delays in: (i) seeking medical attention, (ii) receiving their diagnosis and (iii) commencing treatment. Content analysis was used to map self‐reported reasons for perceived delays at each step, which were then categorised based on the perceived source: (i) personal, (ii) healthcare professional, (iii) healthcare system or (iv) other. The self‐reported reasons and perceived sources were summarised using descriptive statistics. Results Six hundred and eighty‐six rural cancer survivors completed the interview (18% breast, 15% head and neck, 12% prostate and 12% skin cancer). Almost half (n = 320, 47%) of participants perceived a delay at one or more steps. Delays in seeking medical attention were perceived by 132 (19%) participants, mostly related to personal factors (n = 67, 51%), including misinterpreting (n = 19, 28%) signs and symptoms. Delays in diagnosis were perceived by 161 (23%) participants, mostly related to healthcare professional factors (n = 86, 53%), including requiring further opinions or testing for diagnosis (n = 30, 35%). Delays in commencing treatment were perceived by 157 (23%) participants, mostly due to healthcare system factors (n = 57, 37%), including long waitlists (n = 39, 68%). Of the participants who perceived a delay in commencing treatment, comparison with timeframes recommended in the relevant Optimal Care Pathway identified that 57% of perceived delays were actual delays. Conclusions Perceived delays in the pathway to initial cancer detection and treatment are common among rural cancer survivors. Improvements in patient–clinician communication could reduce perceived delays, particularly in diagnosis and treatment. Promoting early help‐seeking, participation in cancer screening and improving access to diagnostic and treatment infrastructure may also improve care experiences.